Developing globally competent researchers: An international perspective - Niemczyk, E.K. (South African Journal of Higher Education, 2020)
Research capacity development is increasingly becoming important worldwide. The ever-changing research landscape driven by globalisation, technological advancements, and the use of new methodologies calls for globally competent researchers. Yet, little is known about research knowledge, skills and values that globally competent researchers need to engage ethically and competently in research projects and research communities across disciplines and across geographic borders. Informed by an international community of 38 scholars in Education from 17 countries of Global South and Global North, this forward-looking study provides a much-needed emerging definition for a globally competent researcher and competencies required by such a researcher. Furthermore, the preliminary findings showcase research learning opportunities and challenges associated with training globally competent researchers. As evident from the findings, more attention needs to be devoted to understanding the preparation of future researchers able to conduct quality research in the interconnected world. The article has potential to be informative to a wide audience from the research world, including professors, researchers, graduate students, research personnel and management.